VD_FINDINFO 23/2014 vom 6. Juni 2014 - VD Tribunal cantonal (2014)
RÉCUSATION, PREMIÈRE INSTANCE, INTERDICTION DE L'ARBITRAIRE, TRIBUNAL FÉDÉRAL | 106 al. 1 CPC (CH), 47 al. 1 let. f CPC (CH), 8a al. 5 CDPJ